Quantifying phosphorus-biochar interactions to determine effectiveness of biochar as a sustainable soil improver - Brian, Kathryn Rose (2019)
The global population is increasing and will reach 9.7 billion by 2050, which, coupled with finite global phosphorus (P) reserves estimated to run out by 2030, places a clear strain on crop production systems. The essential nature of phosphorus for crop growth has led to the exploration of alternative phosphorus resources. Char, also known as biochar, is produced through carbonisation of waste materials in an oxygen-deficient environment and has potential as a soil fertiliser or improver (depending on feedstock used). Biochar can contribute P to soils and solutions in a process known as desorption and also removes P from soils and solutions by sorption. The interactions between chars and P vary from one char to another and alter according to soil type and texture due to different physicochemical properties of both chars and soils. Char/P interactions are important in determining phosphate availability to growing plants and understanding these dynamics before amending soils with char is therefore important. This project aimed to quantify char/P interactions across nine chars made from different feedstocks and/or production temperatures in order to understand which chars would be most suited to conserving or releasing P, both important processes in enhancing P sustainability. The approach was laboratory-based, focusing on batch P sorption experiments and speciation modelling within solutions in addition to soil-char incubation experiments. Char characterisation showed each of the nine chars used had unique chemical and physical properties which were influenced by production mechanism, feedstock and temperature. As a result of the varied physicochemical characteristics, each of the chars displayed different abilities to sorb P from solutions and the sorption behaviours were influenced by feedstock to a greater extent than by production regime. Upon further developing the sorption studies for three of the chars it was observed that adsorption, as oppose to solid-phase precipitation, drove the P removal observed within solutions. The mechanism of adsorption remained unique to each char, where physical surface area likely drove sorption in gasified softwood chars (GSW) and anion exchange of P with oxygen-containing surface functional groups governed sorption in coffee and hardwood chars (HW). Addition of GSW, coffee and HW to acidic, neutral and calcareous soils showed the ability of biochar to influence soil P availability varied according to char and soil physicochemical characteristics. Each char behaved differently within each soil suggesting soil characteristics had a greater impact on P availability than char properties and highlighting how a ‘one-char-fits-all’ approach is not suitable when using char as a soil amendment and a potential source of P. Further studies in mapping char-soil-phosphorus interactions are necessary to understand which soils will benefit from char addition.